2007
DOI: 10.1002/ptr.2189
|View full text |Cite
|
Sign up to set email alerts
|

Identification of campesterol from Chrysanthemum coronarium L. and its antiangiogenic activities

Abstract: Campesterol, a plant sterol in nature, is known to have cholesterol lowering and anticarcinogenic effects. Since angiogenesis is essential for cancer, it was surmised that an antiangiogenic effect may be involved in the anticancer action of this compound. This study investigated the effect of campesterol on basic fibroblast growth factor (bFGF)-induced angiogenesis in vitro in human umbilical vein endothelial cells (HUVECs) and an in vivo chorioallantoic membrane (CAM) model. Campesterol isolated from an ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(68 citation statements)
references
References 29 publications
3
62
0
3
Order By: Relevance
“…b-Sitosterol consumption did not affect the growth of the breast cancer cells in 17b-estradiol-untreated mice, but reduced tumor growth in 17b-estradiol-treated mice by 38.9%. Similarly, Choi et al (2007) determined the effect of campesterol at 10-20 mg/ml on basic fibroblast growth factorinduced angiogenesis in the chorioallantoic membrane of fertilized chicken eggs and reported reduced vascularization in the membrane in a concentration-dependent manner. Quilliot et al (2001), however, failed to observe any effect of phytosterol ingestion (24 mg per rat per day) on colon cancer in rats fed a diet with normal or high saturated fatty acids.…”
Section: Effect Of Phytosterol Intake On Cancer Development In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…b-Sitosterol consumption did not affect the growth of the breast cancer cells in 17b-estradiol-untreated mice, but reduced tumor growth in 17b-estradiol-treated mice by 38.9%. Similarly, Choi et al (2007) determined the effect of campesterol at 10-20 mg/ml on basic fibroblast growth factorinduced angiogenesis in the chorioallantoic membrane of fertilized chicken eggs and reported reduced vascularization in the membrane in a concentration-dependent manner. Quilliot et al (2001), however, failed to observe any effect of phytosterol ingestion (24 mg per rat per day) on colon cancer in rats fed a diet with normal or high saturated fatty acids.…”
Section: Effect Of Phytosterol Intake On Cancer Development In Humansmentioning
confidence: 99%
“…Choi et al (2007) determined the effect of campesterol on basic fibroblast growth factor-induced angiogenesis in endothelial cells isolated from human umbilical vein, and observed reduced proliferation of the cells on campesterol treatment. Awad et al (2001a) reported reduced invasiveness and adhesiveness of breast cancer cells in vitro on b-sitosterol treatment by 78 and 15%, respectively, compared with the control.…”
Section: Inhibition Of Angiogenesis and Metastasis By Phytosterolsmentioning
confidence: 99%
“…While M. paniculata came in the second rank and give ICR 50R 65.1 μg/ml (A549 cells) with inhibition 77.3% at 100µg/ml. In these regards, Choi et al [44] and Lopes et al [45] found that phytosterols have anti-cancer effects, against stomach cancer [46], lung cancer [47], ovary [48] and breast cancer [49] by enhancing stimulation of X-receptor and switch of sphingomyelin, suppression of cell division and induce apoptosis by activation of caspase [50]. It has been speculated that phytosterols inhibit cancer-cell growth, metastasis, invasion, and induce apoptosis [51].…”
Section: Anti-tumor Activitymentioning
confidence: 99%
“…In vitro, human umbilical vein endothelial cells (HUVECs) are isolated from fresh human umbilical cord veins by collagenase treatment (Jaffe et al, 1973) and their proliferation is determined by viability assays such as 2, 3-bis (2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenylamino) carbonyl]-2H-tetrazolium hydroxide (XTT) (Jost et al, 1992), 3-[4,5-dimethyl(thiazol-2yl)-3,5-diphery] tetrazolium bromide (MTT) (Carmichael et al, 1987) or bromophenoluridine (BrdU) incorporation assay in the absence or presence of bFGF or VEGF. Chemotactic migration or motility of HUVECs is assayed by the wound-healing assay or microchemotaxis chambers (Choi et al, 2007) or transwell (Pyun et al, 2008). Differentiation is determined by tube formation assay using HUVEC seeded on Matrigel with or without angiogenic activator (Grant et al, 1992).…”
Section: Endothelial Responses and Assay Models For Screening Potentimentioning
confidence: 99%
“…Naturally occurring gallotannin, penta-1,2,3,4,6-O-galloyl-beta-d-glucose (PGG) isolated from Gallnut of Rhus chinensis MILL was reported to inhibit the proliferation, migration and tube formation of endothelial cells (Huh et al, 2005;Zhang et al, 2009) and also induce apoptosis in prostate cancer cells (Hu et al, 2008;Hu et al, 2009). Antiangiogenic activities have been reported for paeonol (Kim et al, 2009c), shikonin , campesterol (Choi et al, 2007), heyneanol A (Lee et al, 2006a), 6-(1-oxobutyl)-5,8-dimethoxy-1,4-naphthoquinone , Korean Angelica gigas and herbal formulations such as Kamikaekyuktang (Lee et al, 2006b), Shiquandabutangjiaweibang and Bojungbangdocktang (Kim et al, 2009b). In addition, Wang and colleagues demonstrated that feiyanning decoction (FD), a traditional Chinese herbal mixture, has inhibitory effects on angiogenesis by down-regulating the transcription factor nuclear factor kappa B (NF-κB), survival protein Akt and hypoxia inducible factor 1-alpha (HIF-α) in A549 lung cancer cells Wang et al, 2009).…”
Section: Antiangiogenetic Activities Of Medicinal Herbs and Phytochemmentioning
confidence: 99%